Influences of rotation and mass and heat transfer on MHD peristaltic transport of Casson fluid through inclined plane - N.M. Hafez; A.M. Abd-Alla; T.M.N. Metwaly (Alexandria Engineering Journal, 2023)
In the present analysis, we discussed the influence of heat and mass transfer on the hydro-magnetic peristaltic flow of a Casson fluid in a rotating inclined system through an asymmetric channel. The model governing equations are obtained, simplified by applying long wavelength and assumptions of low Reynolds number, and then addressed analytically. DSolve command of Mathematica software was used to solve these equations. The numerical results regarding the impacts of embedded parameters on axial velocity, secondary velocity, stream function, temperature, concentration, and streamline patterns are graphed and explained. It has been discovered that velocity slip reduces the size of the trapped bolus while the permeability parameter increases it. The velocity and temperature profiles decrease as the Casson fluid parameter and magnetic field strength increase. In the fields of biomedical engineering and crude oil refinement, the current problem is quite significant. The trapping phenomenon for different parameters is presented. The visual discussion of numerical results for various values of relevant physical parameters. The current work, which focuses on electromagnetic peristaltic pumps, offers several applications in biomedical engineering.